THE MALE PERSPECTIVE: BLACK AFRICAN MEN’S HAIR PREFERENCES ON BLACK AFRICAN WOMEN - INSIGHTS FROM SOUTH AFRICA - Khulekani Madlela (Universitas PGRI Madiun, 2022)
Drawing on phenomenological perspectives and black feminism, particularly intersectionality, this article uses a qualitative questionnaire to examine the hair preferences of black African men on black African women. The article explores whether black African men prefer long, straight hair in black women. Using intersectionality as a theoretical lens, this article further examines discourses that shape black African men’s hair preferences, perceptions and attitudes towards hair enhancements and hair alteration. Previous studies have shown that black African women alter their hair because they believe that black African men are attracted to women with long hair. Through examining the male gaze and the policing of women’s bodies, this article uncovered what black African men consider to be the African beauty ideals. The findings from my research revealed that contrary to black African women’s assumptions, black African men do not consider long, straight hair to be the standard of beauty. On the one hand, long hair was associated with beauty, femininity, and dignity while on the other hand, it was perceived as disruptive and expensive to maintain. These findings revealed that the selected men are not as enamoured with long hair as black African women believe them to be but are more appreciative of different hair types, textures, lengths, and hairstyles. The men’s hair perceptions and views are shaped by factors including their own personal preferences, family members, religion, and on-going hair debates in South Africa.